ENHANCING STUDENTS’ WRITING SKILL THROUGH TASK-BASED APPROACH - Ari Widayanti, Maria Johana (Universitas Negeri Semarang, 2011)
Writing is a communicative action where there is an interaction process between writer andreaders through a text. The relationship has a value as the final result to decide what amessage the writer wants to give to the readers. The writing process implies to the text itselfwhich contains a cooperative work between writer and readers. Task based approach is analternative language learning that is based on tasks. Students have to do and complete someexercises that are given by a teacher. While the writing process is an action to produce alanguage as naturally as speaking process. Through writing, we communicate our ideas toreaders. Journalism, as a subject for English students in our department, aims to give a writingskill for students by following journalism’s norms. Therefore, the writing skill is importantbecause through writing, students can write a news story in English language that can bepublished in a newspaper following the Journalism norms.